Body size shapes inter‐specific migratory behaviour: evidence from individual tracks of long‐distance migratory shorebirds. (5th February 2018) - Zhao, Meijuan; Christie, Maureen; Coleman, Jonathan; Hassell, Chris; Gosbell, Ken; Lisovski, Simeon; Minton, Clive; Klaassen, Marcel
Abstract : Migration is a common phenomenon across many animal taxa. Understanding how migration scales with body size across species is fundamental in the development of migration theory and in making size‐related predictions. Although aerodynamic theory and ecophysiological scaling laws have assisted greatly in generating such predictions, their verifications have been limited by a lack of empirical data across a range of body sizes. The recent development of ultra‐light tracking devices and its rapid application to migration now allows us to put theory to the test. We used tracking data of seven closely related migratory sandpiper species (family Scolopacidae) along the East Asian‐Australasian Flyway to compare their migratory behaviour when migrating towards the breeding grounds as a function of size (50–750 g). We found a marked decline in migration speed (migration distance divided by total migration duration, including time at stopover sites and in flight) with size. Departure date from the non‐breeding (i.e. wintering) ground and arrival date at the breeding ground also scaled negatively with size. Total migration duration, migration distance, total staging duration (the number of days staying at stopover sites plus days preparing, i.e. fuelling, prior to initial migration) and step length (distance covered within one migratory leg) were not significantly related with size. Correction for phylogeny showed consistent results for all variables. Besides improving our fundamental understanding of inter‐specific variation in migration behaviours, the finding of a clear scaling with size in migration speed and migration timing highlight differential size related capabilities and constraints of migrants. Migratory birds, including sandpipers, are declining on a global scale and particularly along the East Asian‐Australasian Flyway. This notion of size‐dependency in migratory traits may have a bearing on their vulnerability to specific environmental disturbances along their flyways.